Implementation of an Electronic Health Records–Based Safe Contrast Limit for Preventing Contrast-Associated Acute Kidney Injury After Percutaneous Coronary Intervention. Issue 1 (7th December 2022) - Yuan, Neal; Zhang, Justin; Khaki, Rakan; Leong, Derek; Bhoopalam, Chandrashekhar; Tabak, Steven W.; Elad, Yaron; Pevnick, Joshua M.; Cheng, Susan; Ebinger, Joseph E.
Abstract : Background: Contrast-associated acute kidney injury (CA-AKI) after percutaneous coronary intervention is associated with increased mortality. We assessed the effectiveness of an electronic health records safe contrast limit tool in predicting CA-AKI risk and reducing contrast use and CA-AKI. Methods: We created an alert displaying the safe contrast limit to cardiac catheterization laboratory staff prior to percutaneous coronary intervention. The alert used risk factors automatically extracted from the electronic health records. We included procedures from June 1, 2020 to October 1, 2021; the intervention went live February 10, 2021. Using difference-in-differences analysis, we evaluated changes in contrast volume and CA-AKI rates after contrast limit tool implementation compared to control hospitals. Cardiologists were surveyed prior to and 9 months after alert implementation on beliefs, practice patterns, and safe contrast estimates for example patients. Results: At the one intervention site, there were 508 percutaneous coronary interventions before and 531 after tool deployment. At 15 control sites, there were 3550 and 3979 percutaneous coronary interventions, respectively. The contrast limit predicted CA-AKI with an accuracy of 64.1%, negative predictive value of 93.3%, and positive predictive value of 18.7%. After implementation, in high/modifiable risk patients (defined as having a calculated contrast limit <500ml) there was a small but significant −4.60 mL/month (95% CI, −8.24 to −1.00) change in average contrast use but no change in CA-AKI rates (odds ratio, 0.96 [95% CI, 0.84–1.10]). Low-risk patients had no change in contrast use (−0.50 mL/month [95% CI, –7.49 to 6.49]) or CA-AKI (odds ratio, 1.24 [95% CI, 0.79–1.93]). In assessing CA-AKI risk, clinicians heavily weighted age and diabetes but often did not consider anemia, cardiogenic shock, and heart failure. Conclusions: Clinicians often used a simplified assessment of CA-AKI risk that did not include important risk factors, leading to risk estimations inconsistent with established models. Despite clinician skepticism, an electronic health records–based contrast limit tool more accurately predicted CA-AKI risk and was associated with a small decrease in contrast use during percutaneous coronary intervention but no change in CA-AKI rates.